Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms232112978
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic-Induced Oxidative Stress in Metolachlor-Degrading Filamentous Fungus Trichoderma harzianum

Abstract: While there has been intensive research on the influence of microplastics (MPs) on aquatic organisms and humans, their effect on microorganisms is relatively little-known. The present study describes the response of the Trichoderma harzianum strain to low-density polyethylene (LDPE) microparticles. MPs, either separately or with metolachlor (MET), were added to the cultures. Initially, MP was not found to have a negative effect on fungal growth and MET degradation. After 72 h of cultivation, the content of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 74 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…However, the influence of MPs on microorganism metabolic activity (e.g., herbicide biodegradation or biosurfactant production) is rarely researched. One such paper was that of Jasińska et al 34 , who reported that MPs induced oxidative stress in the MET-degrading filamentous fungus T. harzianum .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the influence of MPs on microorganism metabolic activity (e.g., herbicide biodegradation or biosurfactant production) is rarely researched. One such paper was that of Jasińska et al 34 , who reported that MPs induced oxidative stress in the MET-degrading filamentous fungus T. harzianum .…”
Section: Resultsmentioning
confidence: 99%
“…After centrifugation, the top layer was collected. 2,4-D and MET contents were analysed according to the methods described by Nykiel et al 33 and Jasińska et al 34 , respectively. Briefly, 2,4-D content was measured using an Agilent 1200 HPLC system (Agilent, USA) and a 3200 Q-TRAP mass spectrometer (Sciex, USA) equipped with an ESI source.…”
Section: Methodsmentioning
confidence: 99%